The Effects of "Mindfulness Meditation for Pain Management" on the Severity of Perceived Pain and Disability in Patients With Chronic Pain - Farzaneh Mohammadi; Parvaneh Mohammadkhani; Behrooz Dolatshahi; Mohammad Ali Asghari (University of Social Welfare & Rehabilitation Sciences, 2011)
Objectives: This study aimed at investigating the effectiveness of Mindfulness Based Cognitive Therapy (MBCT) in management of pain and functional limits of chronic pain patients. Methods & Materials: In this semi-experimental study, 30 volunteer female patients suffering from chronic pain attending a clinical assessment for treatment of chronic pain were recruited using the convenience sampling. Then, they were randomized to intervention or control group. Both groups completed the graded classification of chronic pain and pain disability questionnaires. The intervention lasted approximately 8 weeks. Data was analyzed by descriptive and covariance analysis. Results: Our results indicated that the severity of perceived pain (P=0.001) and disability caused by pain (P=0.04) in intervention group decreased significantly in comparison with the control group. Conclusion: The results suggest that themindfulness intervention can decrease the severity of perceived pain and disability in chronic pain patients.